2016
DOI: 10.2319/061916-481.1
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam computed tomography versus periapical radiograph for diagnosing external root resorption: A systematic review and meta-analysis

Abstract: Objective: To compare the diagnostic accuracy of cone-beam computed tomography (CBCT) and periapical radiographs (PR) for the detection of external root resorption (ERR). Material and Methods: An electronic search in databases, including the Cochrane Central Register of Controlled Trials, PubMed, Embase, the China National Knowledge Infrastructure, and System for Information on Grey Literature in Europe (SIGLE), was performed until August 2016. A manual search of relevant journals and reference lists of enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 29 publications
3
54
0
4
Order By: Relevance
“…Most of those previous studies on orthodontic ARR was performed using two-dimensional radiography, such as panoramic and periapical radiographs. CBCT has shown advantages in the accuracy and efficacy for diagnosis and measurement of root resorptio n [23]. A number of previous studies used CBCT to evaluate the ARR in patients with fixed appliances and found the frequency of ARR was more than 70% in incisor s [9].…”
Section: Discussionmentioning
confidence: 99%
“…Most of those previous studies on orthodontic ARR was performed using two-dimensional radiography, such as panoramic and periapical radiographs. CBCT has shown advantages in the accuracy and efficacy for diagnosis and measurement of root resorptio n [23]. A number of previous studies used CBCT to evaluate the ARR in patients with fixed appliances and found the frequency of ARR was more than 70% in incisor s [9].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, three-dimensional (3D) cone-beam computed tomography (CBCT) has been successfully used to evaluate ARR in 3D space. 17 Future studies using 3D CBCT may demonstrate more direct associations between ARR and ARD.…”
Section: Discussionmentioning
confidence: 99%
“…28,12,24 Thus, accurate diagnosis of the presence and extent of the lesion of root resorption is only possible through three-dimensional radiographic examination such as the computed tomography. 16,29 In…”
Section: Discussionmentioning
confidence: 99%